Principios básicos de la cromatografía líquida de alto rendimiento para la separación y análisis de mezclas (2018)
The implementation of high performance liquid chromatography is increasing because it employs chromatography techniques that were previously unavailable as adsorption chromatography, partition chromatography, molecular exclusion chromatography and affinity chromatography. This article discloses the basic concepts of HPLC and how the separation and/or analysis of a sample using high performance liquid chromatography can be satisfactorily addressed.